Design and Characterization of a Centrifugal Compressor Surge Test Rig - Kin Tien Lim; Se Young Yoon; Christopher P. Goyne; Zongli Lin; Paul E. Allaire (International Journal of Rotating Machinery)
A detailed description of a new centrifugal compressor surge test rig is presented. The objective of the design and development of the rig is to study the surge phenomenon in centrifugal compression systems and to investigate a novel method of surge control by active magnetic bearing servo actuation of the impeller axial tip clearance. In this paper, we focus on the design, initial setup, and testing of the rig. The latter two include the commissioning of the rig and the experimental characterization of the compressor performance. The behavior of the compressor during surge is analyzed by driving the experimental setup into surge. Two fundamental frequencies, 21 Hz and 7 Hz, connected to the surge oscillation in the test rig are identified, and the observed instability is categorized according to the intensity of pressure fluctuations. Based on the test results, the excited pressure waves are clearly the result of surge and not stall. Also, they exhibit the characteristics of mild and classic surge instead of deep surge. Finally, the change in the compressor performance due to variation in the impeller tip clearance is experimentally examined, and the results support the potential of the tip clearance modulation for the control of compressor surge. This is the first such demonstration of the feasibility of surge control of a compressor using active magnetic bearings.